Emotional knowledge and aesthetic of self: the perspective of floral medicine - Pedraza Gómez, Zandra (2007)
This article studies the main anthropological features implicit in the conception of floral therapy and its use as an expression of a type of emotional knowledge that reveals changes in terms of Norbert Elías’ model of affection control, which characterizes the civilization process according to said author. The increasingly widespread use of this kind of therapies suggests that subjectivity has not only achieved greater importance in today’s contemporary anthropological conception, but also that it is strongly connected to the notion of corporality and to an aesthetics-politics that enhances the contemporary analytical scope of the concept of biopower.